2020
DOI: 10.2166/washdev.2020.157
|View full text |Cite
|
Sign up to set email alerts
|

Household levels of deprivation to WaSH and residential conditions in slum settlements of Lagos, Nigeria

Abstract: Household levels of deprivation to water, sanitation, and hygiene (WaSH) and residential conditions in slum settlements of Lagos, Nigeria were assessed and mapped using slum deprivation index (SDI). A structured questionnaire was administered to 1,398 households in 16 settlements using a random sampling method. Descriptive statistics and SDI were employed to analyze the data while ArcMap was used to map the patterns of SDI. The results show that households live in poor dwelling conditions with limited access t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…This finding becomes very concerning as the sanitary conditions, in this case, are very similar to our findings. A study in Lagos, Nigeria has also found deprived condition in slum areas in case of water, sanitation, and hygiene, including waterlogging and waste disposal conditions (Akoteyon et al, 2021). As we can see from our study, the overall condition of these sectors in Chittagong is also unsatisfactory.…”
Section: Gendermentioning
confidence: 50%
“…This finding becomes very concerning as the sanitary conditions, in this case, are very similar to our findings. A study in Lagos, Nigeria has also found deprived condition in slum areas in case of water, sanitation, and hygiene, including waterlogging and waste disposal conditions (Akoteyon et al, 2021). As we can see from our study, the overall condition of these sectors in Chittagong is also unsatisfactory.…”
Section: Gendermentioning
confidence: 50%
“…Some studies do provide a separate assessment of sustainability [20,21], inequality [22], governance and poverty [23], vulnerability and security [24] and service gap [25] aspects of water and sanitation services. However, they are either limited to a particular component of the water and sanitation sector, or are conducted at the macro level using secondary data, or are area-specific, or have inadequate indicators to reflect the ground situation [26]. Apart from these, several studies have incorporated certain indicators of the water and sanitation sector in measuring the overall deprivation of material well-being at a macro level [27,28].…”
Section: Dimensions and Variablesmentioning
confidence: 99%
“…Most of these researchers focused on assessing the USSs at the neighbourhood level rather than the household level. A limited number of studies moved beyond the neighbourhood level and assessed the underserved conditions at the household level (Patel, Koizumi & Crooks, 2014;Patel et al, 2019;Patel, Shah & Beauregard, 2020;Akoteyon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%